2017
DOI: 10.1039/c7cp00900c
|View full text |Cite
|
Sign up to set email alerts
|

Extra electronic outer-shell peculiarities accessible under a joint XPS and DFT study

Abstract: Electronic configuration of chemically bound atoms at the surface, including adsorbed species, or in the bulk of a solid contains a set of natural traps for energy absorption provided by valence band transitions or plasmon oscillations. The core level excitation of any origin is generally coupled with those traps, forming a multichannel route for nonradiative energy dissipation. Using an example of Pt and graphitebased materials, the study shows experimental tracing over these channels by means of elastic elec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 40 publications
0
10
0
Order By: Relevance
“…(1). The calculated Pt shake-up and shake-off spectra in Figure 2 are close to each other due to strongly localized vacant states at E F and the 1D DOS at the vacuum level, respectively, and because of domination of the equal d zx , d zy , and d xy states in total DOS [30]. An agreement between experimental and simulated spectral fragments in Figure 2 implies regular involvement of the Pt DOS into CEE events, as well as similar matrix elements f(E, σ) for different partial densities of states (pDOS) in Eq.…”
Section: Ptmentioning
confidence: 52%
See 4 more Smart Citations
“…(1). The calculated Pt shake-up and shake-off spectra in Figure 2 are close to each other due to strongly localized vacant states at E F and the 1D DOS at the vacuum level, respectively, and because of domination of the equal d zx , d zy , and d xy states in total DOS [30]. An agreement between experimental and simulated spectral fragments in Figure 2 implies regular involvement of the Pt DOS into CEE events, as well as similar matrix elements f(E, σ) for different partial densities of states (pDOS) in Eq.…”
Section: Ptmentioning
confidence: 52%
“…DFT calculations have revealed that the Br 2 embedding enlarges the interlayer distance, but insignificantly affects the pDOS of the C, (F) C and F [30]. The latter conforms to chemical inertness of the pristine C 2 F cell and to low Br content in the product C 2 FBr 0.15 [62].…”
Section: Br 2 -Embedded C 2 Fmentioning
confidence: 83%
See 3 more Smart Citations